Phytochemical Analysis of Ethanolic extract of leaf of Azadirachta indica and in vitro Acaricidal Effect against Rhipicephalus microplus - Dalei, Manas Kumar; Dehur, Manaswini; Mohanty, Bijayendranath; Hembram, Ananta; Palai, Santwana; Kuppusamy, Senthil (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The continuous use of chemical ectoparasiticides leads to development of acaricide resistance in ticks. The present study was focused on evaluation of in vitro acaricidal efficacy of ethanolic extract of Azadirachta indica leaf against Rhipicephalus microplus as well as phyto analysis of A. indica leaf extract. The phytochemicals in ethanolic extract of A. indica leaf was assessed by Gas chromatography-Mass spectroscopy (GC-MS) and Fourier Transform Infra-red Spectroscopy (FTIR). The larvicidal and acaricidal effect of ethanolic extract was investigated by Adult Immersion Test (AIT) and Larval Packet Test (LPT). The FTIR analysis showed presence of carboxylic acids, alkynes, amides, aromatic esters and alkyl hallides as the functional group and GC-MS revealed presence of components; Hexadecanoic acid, octadeca-9,12,15-trienoic acid, 2-(2,5-dimethoxy-4-methylphenyl) ethanamine, 4-ethyl-1,2-dimethoxybenzene.The adult tick mortality, reproductive index, Inhibition of oviposition and larval mortality was observed 86.687%,: 0.038,: 92.59% and 78.67%, respectively at highest concentration of extract (100 mg/mL) and LC50 value was determined to be 29.21 mg/mL. There was dose-dependant mortality of adult, larva ticks and reproductive parameters. These results showed that ethanolic extract of A. indica leaves is a good source of bioactive phytochemicals with antitick activities.